Evaluasi Penggunaan Aplikasi E-Coklit Oleh PPS Dalam Pemutakhiran Data Pemilih Pada Pemilu Tahun 2024 (Studi Pada Desa Sinar Ogan Kecamatan Tanjung Bintang Kabupaten Lampung Selatan) - Miftaul Zana Prihatini; Nur Islam; Tia Marlinda Sari (Journal Ilmu Sosial, Politik dan Pemerintahan, 2024)
General elections are the main foundation in running a democratic system, and updating voter data is a critical aspect in ensuring the integrity and validity of the process. This research aims to evaluate the effectiveness and impact of using the E-Coklit application by PPS in updating voter data for 2024 in Sinar Ogan Village. This research uses a qualitative method with a case study approach. Data was collected through in-depth interviews with PPS members, participatory observation of the data updating process, and analysis of documents related to the implementation of the general election. Through this approach, the research gained an in-depth understanding of the use of the E-Coklit application by PPS and its impact on updating voter data. The evaluation results show that the use of the E-Coklit application by PPS in Sinar Ogan Village makes a positive contribution to the efficiency of updating voter data. Transparency and accountability of the general election process have also increased through real-time data disclosure.